NEW WAYS OF WORKING WITH STUDENTS - Qoraboyev , Fazliddin Faxriddinovich (Educational Research in Universal Sciences, 2023)
The article is published in order to be able to correctly choose educational methods based on best practices in conveying the secrets of science to students, to effectively approach the formation of students’ knowledge, skills and abilities.